2013
DOI: 10.4103/2279-042x.117389
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Punica granatum extract in the management of recurrent aphthous stomatitis

Abstract: Objective:Recurrent aphthous stomatitis (RAS) is a common, painful ulcerative disorder of the oral cavity with unknown etiology. No documented cure exists and topical application of medications aims to reduce pain associated with this condition. The aim of this study was to evaluate the efficacy of Punica granatum (PG) extract on the clinical management of RAS.Methods:A total of 40 patients with RAS participated in this randomized, double-blind, and placebo-controlled study. During three episodes of RAS, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…The results of the study suggest that PG with a mean healing time of 5.3 days can be a proper alternative for the clinical management of RAS. The results also showed that the mean time for pain elimination after therapy with Z. multiflora extract, A. nobelis extract, mixture of these two, and M. communis mouth rinse was 3 days, 5 days, 3.1 days, and 4 days, respectively 21 . PG with a mean pain elimination time of 3.4 days was shown to have a comparable effect with other herbal agents in the management of RAS symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…The results of the study suggest that PG with a mean healing time of 5.3 days can be a proper alternative for the clinical management of RAS. The results also showed that the mean time for pain elimination after therapy with Z. multiflora extract, A. nobelis extract, mixture of these two, and M. communis mouth rinse was 3 days, 5 days, 3.1 days, and 4 days, respectively 21 . PG with a mean pain elimination time of 3.4 days was shown to have a comparable effect with other herbal agents in the management of RAS symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…Considering these pharmacological effects of pomegranate flower extract and the preliminary studies indicating effectiveness of pomegranate flower extract on aphthous ulcers. 16 We decided to utilize these effects and design a suitable, stable and easily accessible formulation of this herb. The folin-ciocalteu , s method was used to indicate the amount of poly-phenols in dried extract.…”
Section: Discussionmentioning
confidence: 99%
“…15 Considering these side effects and based on preliminary studies on pomegranate flower effectiveness on aphthous ulcers. 16 We prepare a stable mucoadhesive formulation of pomegranate flower that can be used as an alternative treatment for aphthous stomatitis. ethanol, gallic acid, sodium carbonate were prepared from Merck Company (Germany) and Folin-ciocalteu's indicator was purchased from Sigma Aldrich Company (Germany).…”
mentioning
confidence: 99%
“…It is a multifactorial disease and several predisposing and risk factors have been implicated in its pathogenesis. Due to uncertain etiology and unpredictable course of the disease, there is no definitive treatment for RAS (2). Treatment strategies therefore aim at relieving pain, promoting healing and preventing secondary infection (3).…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural products, including medicinal plant preparations for pain reduction and shortening of healing time of oral aphthous ulcers are gaining more attention due to their decreased side effects and drug resistance (2). …”
Section: Introductionmentioning
confidence: 99%